Land suitability evaluation of Philippine sunflower (Helianthus annuus L.) for potential conversion to biodiesel - Cerame, Aaron John V. (Animo Repository, 2022)
The emergence of sunflower in the bioenergy sector is slowly being established as a sustainable response to the increasing demand for food and energy. Growing bioenergy crops with the objective of maximizing their yield is a complex process that requires a proper land suitability analysis to select the most suitable crop for a specific soil location. This research assessed the bioenergy potential in terms of actual energy produced of Philippine Sunflower (Helianthus annuus L.) based on its land suitability and availability in the Philippines. The availability and suitability analysis were performed through the ArcGIS ArcMAP software to generate maps that provided the total suitable available lands for sunflower plantation. Results showed that 15,683.80 thousand ha of lands are available. Out of all the available lands, 19.96% is suitable for sunflower plantation when considering S1 and S2 classifications. From the identified areas, the percentage differences of all the actual and theoretical energy of biodiesel produced are 51.09% which may be attributed to the insufficient data for the energy requirement of various sunflower plants to produce biodiesel. This study supports the mandate of the 2006 Biofuels Act (RA 9367) by reducing the reliance on imported fuels and non-renewable energy. Moreover, this study also supports the Philippines' National Food Policy (NFP) by providing an oilseed-based alternative source of feedstock to minimize allocation. It is recommended to conduct a multi criteria study in terms of the growth parameters of the sunflower to further improve the accuracy of the data produced and to conduct an in-depth analysis of the high suitability regions for sunflower plantation.